2001
DOI: 10.1088/1126-6708/2001/04/035
|View full text |Cite
|
Sign up to set email alerts
|

Bekenstein bounds in de Sitter and flat space

Abstract: The D-bound on the entropy of matter systems in de Sitter space is shown to be closely related to the Bekenstein bound, which applies in a flat background. This holds in arbitrary dimensions if the Bekenstein bound is calibrated by a classical Geroch process. We discuss the relation of these bounds to the more general bound on the entropy to area ratio. We find that black holes do not saturate the Bekenstein bound in dimensions greater than four.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
165
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(172 citation statements)
references
References 24 publications
7
165
0
Order By: Relevance
“…This inequality is obtained by considering the classical absorption of the system by a large black hole; it does not depend on the dimension of spacetime [6]. Bekenstein's bound is remarkably tight (consider, for example, a massive particle in a box the size of its Compton wavelength).…”
mentioning
confidence: 99%
“…This inequality is obtained by considering the classical absorption of the system by a large black hole; it does not depend on the dimension of spacetime [6]. Bekenstein's bound is remarkably tight (consider, for example, a massive particle in a box the size of its Compton wavelength).…”
mentioning
confidence: 99%
“…A year later Hawking found a quantum evaporation of a black hole [3,4] which gave the birth to thermodynamics of black holes [5][6][7] (for a review see [8]). In 1976 Gibbons and Hawking found that also cosmological horizon can radiate [9], and this gave rise to thermodynamics of horizons [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A well known example for the AdS-CFT is given by the microscopical description of the thermodynamical laws of black holes [3]. Furthermore, applications of the de Sitter space Bousso bound [4], related to the Bekenstein bound for flat space-times, have also drawn much interest.…”
Section: Introductionmentioning
confidence: 99%
“…A well known example for the AdS-CFT is given by the microscopical description of the thermodynamical laws of black holes [3]. Furthermore, applications of the de Sitter space Bousso bound [4], related to the Bekenstein bound for flat space-times, have also drawn much interest.The dS-CFT correspondence has not yet reached the degree of comprehension of the AdS-CFT, since the corresponding CFT has not been completely identified. Therefore, one usually proceeds by studying simplified "gravitational" models in order to obtain general features that the relevant CFT is required to possess.…”
mentioning
confidence: 99%
See 1 more Smart Citation